Analysis of the results of Structural Surveys of russian Business for 2017–2022 - L. Yu. Arkhangel’skaya; O. Yu. Sitnikova (Учёт. Анализ. Аудит, 2023)
The development of business structures with a different scales of activity, as well as individual entrepreneurship (IE) is the basis of the economy of any country, the source of creating highly efficient jobs, the basis for introducing innovations; therefore, in all countries of the world, structural survey programs are implemented annually, including a unified system of indicators — business organizations and individual entrepreneurs act as objects of continuous annual monitoring by national statistical services. In this regard, the purpose of the study — that is to study the patterns of demography of Russian enterprises and changes in their business activity in 2017–2022 — is so relevant. The work used a selective method of observation, methods of dynamic and correlation-regression types of analysis. The authors studied the structure of the totality of Russian business organizations, their distribution by federal districts according to such criteria as the birth rate (economic birth rate), official liquidation (mortality), structural shifts in their demography in 2022 compared to 2017. In the course of the study trends in changes in the levels of fertility and mortality of organizations were determined and short-term forecasts of their values for 2023 were built. The authors also present the results of an analysis of the development of individual entrepreneurship in the Russian Federation for 2017–2021. The results of the study can be used both in territorial statistical services and in Rosstat, and can also be used to train economists, analysts, statisticians in universities of a financial and economic profile, in scientific organizations, in the system of regional and state administration for the development of socio-economic policy.